Oropharyngeal microbiome profiled at admission is predictive of the need for respiratory support among COVID-19 patients - Bradley, Evan S.; Zeamer, Abigail L.; Bucci, Vanni; Cincotta, Lindsey; Salive, Marie-Claire; Dutta, Protiva; Mutaawe, Shafik; Anya, Otuwe; Tocci, Christopher; Moormann, Ann; Ward, Doyle V.; McCormick, Beth A.; et al. (Frontiers in Microbiology, 2022)
The oropharyngeal microbiome, the collective genomes of the community of microorganisms that colonizes the upper respiratory tract, is thought to influence the clinical course of infection by respiratory viruses, including Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus Infectious Disease 2019 (COVID-19). In this study, we examined the oropharyngeal microbiome of suspected COVID-19 patients presenting to the Emergency Department and an inpatient COVID-19 unit with symptoms of acute COVID-19. Of 115 initially enrolled patients, 50 had positive molecular testing for COVID-19+ and had symptom duration of 14 days or less. These patients were analyzed further as progression of disease could most likely be attributed to acute COVID-19 and less likely a secondary process. Of these, 38 (76%) went on to require some form of supplemental oxygen support. To identify functional patterns associated with respiratory illness requiring respiratory support, we applied an interpretable random forest classification machine learning pipeline to shotgun metagenomic sequencing data and select clinical co-variates. When combined with clinical factors, both species and metabolic pathways abundance-based models were found to be highly predictive of the need for respiratory support (F1-score 0.857 for microbes and 0.821 for functional pathways). To determine biologically meaningful and highly predictive signals in the microbiome, we applied the Stable and Interpretable RUle Set (SIRUS) to the output of the models. This analysis revealed that low abundance of two commensal organisms, Prevotella salivae or Veillonella infantium (less than 4.2% and 1.7% respectively), and a low abundance of a pathway associated with LPS biosynthesis (less than 0.1%) were highly predictive of developing the need for acute respiratory support (82% and 91.4% respectively). These findings suggest that the composition of the oropharyngeal microbiome in COVID-19 patients may play a role in determining who will suffer from severe disease manifestations.